Orbitally and geographically caused seasonal asymmetry in Titan's tropospheric climate and its implication for the lake distribution - Tokano, Tetsuya (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
Previously, seasonal asymmetry in Titan's climate caused by Saturn's orbital eccentricity was proposed as a possible external cause of the asymmetric polar lake distribution on Titan. However, climate studies of other planets indicate that seasonal asymmetry can also be caused by a hemispheric asymmetry in geography such as the ocean-continent distribution or topography. A global climate model is used to investigate whether orbital forcing or hemispheric asymmetry in geography is more important for the seasonal asymmetry in Titan's climate and the distribution of polar methane deposits. Titan's large-scale topography generally decreases from equator to pole and thereby induces meridional circulation with upwelling at low latitudes and downwelling at high latitudes due to near-surface horizontal temperature gradients. This circulation is stronger in the southern hemisphere, which contains steep slopes at mid latitudes, and acts to transport dry air downward near the south pole and to reduce the precipitation in southern summer. Consequently, the annual precipitation minus evaporation is substantially smaller in the south polar region than in the north polar region. Orbital parameter variations quantitatively affect the polar precipitation, yet are unable to reverse the vast hemispheric asymmetry in the polar precipitation. The accumulation of Titan's lakes near the north pole could therefore be a semipermanent feature related to Titan's topography and may resist the Croll-Milankovitch cycle.